Analisis Ketahanan Pangan Rumah Tangga Petani pada Masa Pandemi Covid-19 - Siti Nurbais; Tito Hardiyanto; Ida Ningrumsari; Amila Khairina (Jurnal Dimamu, 2022)
The COVID-19 pandemic has affected the agricultural sector in the food crop sub-sector, such as decreased food productivity, decreased distribution of production factors and food commodity yields, and increased prices for food products. This also affects the level of farmers' welfare, especially the food security and insecurity of farmers' households. This study aims to determine the resilience and food insecurity of farmer households during the Covid-19 pandemic, a case study in Cimanganten Village, Tarogong Kaler District, Garut Regency. The type of research used is a case study method, the determination of respondents is determined by purposive sampling, namely as many as 12 respondents who come from farmer households who own cereals, legumes and tubers farming in Cimanganten Village. Data analysis was carried out by determining the level of food security seen from the share of food expenditure and food insecurity using the jonsson and tolee method, food security and food insecurity index indicators. The results showed that food security of farm households during the covid-19 pandemic in Cimanganten Village is classified as food security, and food insecurity of farm households during the covid-19 pandemic in Cimanganten Village did not experience food insecurity.